Healthcare resilience in the climate crisis: Do we have any? - Rosa Montero; Isaac Chung; Mark Wright (Future Healthcare Journal)
The UK is increasingly being affected by unpredictable weather events with flooding, heatwaves and storms impacting on physical and mental health and livelihoods. All of these will become increasingly common as the climate crisis accelerates. Efforts made to reduce greenhouse gas (GHG) emissions are slow. Healthcare systems must meet the growing demands of a multi-morbid and ageing population, while simultaneously reducing their environmental impact. The NHS is already under significant pressures and currently is ill-prepared to deal with these changes unless adaptive and resilient measures are introduced urgently and at pace. Hospital infrastructures require urgent vulnerability climate crisis assessment; however, fundamentally the models of care we currently use are dated and in need of innovative solutions that embrace digital technologies to help develop new models of care in the community. Failure to introduce resilience will lead to future preventable deaths. We must act now and do so collaboratively.